Optically efficient InAsSb nanowires for silicon-based mid-wavelength infrared optoelectronics. (8th February 2017) - Zhuang, Q D; Alradhi, H; Jin, Z M; Chen, X R; Shao, J; Chen, X; Sanchez, Ana M; Cao, Y C; Liu, J Y; Yates, P; Durose, K; Jin, C J
Abstract: InAsSb nanowires (NWs) with a high Sb content have potential in the fabrication of advanced silicon-based optoelectronics such as infrared photondetectors/emitters and highly sensitive phototransistors, as well as in the generation of renewable electricity. However, producing optically efficient InAsSb NWs with a high Sb content remains a challenge, and optical emission is limited to 4.0 μ m due to the quality of the nanowires. Here, we report, for the first time, the success of high-quality and optically efficient InAsSb NWs enabling silicon-based optoelectronics operating in entirely mid-wavelength infrared. Pure zinc-blende InAsSb NWs were realized with efficient photoluminescence emission. We obtained room-temperature photoluminescence emission in InAs NWs and successfully extended the emission wavelength in InAsSb NWs to 5.1 μ m. The realization of this optically efficient InAsSb NW material paves the way to realizing next-generation devices, combining advances in III-V semiconductors and silicon.